2020
DOI: 10.1016/j.isci.2020.101713
|View full text |Cite
|
Sign up to set email alerts
|

Caenorhabditis elegans algn-2 Is Critical for Longevity Conferred by Enhanced Nonsense-Mediated mRNA Decay

Abstract: Nonsense-mediated mRNA decay (NMD) is a biological surveillance mechanism that eliminates mRNA transcripts with premature termination codons. In Caenorhabditis elegans, NMD contributes to longevity by enhancing RNA quality. Here, we aimed at identifying NMD-modulating factors that are crucial for longevity in C. elegans by performing genetic screens. We showed that knocking down each of algn-2/asparagine-linked glycosylation protein, zip-1/bZIP transcription factor, and C44B11.1/FAS apoptotic inhibitory molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
(19 reference statements)
0
8
0
Order By: Relevance
“…Twenty-one of these 29 genes, including eol-1 , ddn-1 and the pals genes, were already characterized as part of the IPR (Reddy et al, 2019). Among the rest, math-39 and Y105C5A.9 were identified as dependent of the ZIP-1 transcription factor highly associated with IPR (Lažetić et al, 2022) and positive modulator of non-sense mediated mRNA decay (Kim et al, 2020). This is the first time that col-133 , trpl-5 , math-15 , Y43F8B.12 , and Y6G8.5 have been associated to the worm’s response to OrV.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-one of these 29 genes, including eol-1 , ddn-1 and the pals genes, were already characterized as part of the IPR (Reddy et al, 2019). Among the rest, math-39 and Y105C5A.9 were identified as dependent of the ZIP-1 transcription factor highly associated with IPR (Lažetić et al, 2022) and positive modulator of non-sense mediated mRNA decay (Kim et al, 2020). This is the first time that col-133 , trpl-5 , math-15 , Y43F8B.12 , and Y6G8.5 have been associated to the worm’s response to OrV.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, overexpression of smg-1 , which encodes a protein kinase that activates SMG-2/UPF1, significantly increases lifespan. In our subsequent study that performed genome-wide RNAi and mutagenesis screens to identify NMD modulators, we reported ALGN-2/alpha-1,3/1,6-mannosyltransferase (ALG2) as a positive regulator of NMD ( Kim et al, 2020b ). We showed that ALGN-2 is required for the longevity of daf-2 mutants, and conversely, overexpression of algn-2 increases lifespan.…”
Section: Main Bodymentioning
confidence: 99%
“…First, dietary restriction appears to promote longevity through mRNA processing and quality control in C. elegans and mice ( Tabrez et al, 2017 ). In C. elegans, the prolongevity effect of dietary restriction is mediated by proper alternative splicing ( Heintz et al, 2017 ) coupled with nonsense-mediated decay ( Tabrez et al, 2017 ), which is crucial for the longevity conferred by various interventions ( Kim et al, 2020 ; Son et al, 2017 ). In mice, dietary restriction enhances alternative splicing events in the brain, displaying higher alternative splicing levels than those found in other tissues ( Tabrez et al, 2017 ).…”
Section: Dietary Restrictionmentioning
confidence: 99%